Tinjauan Etikomedikolegal Penanganan Pasien Trauma Di Instalasi Gawat Darurat RSI Banjarnegara - Nitiprodjo, Abdul Hakim; Fitriana, Nurul Fatwati (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Emergency patient services often cause ethical and criminal problems. In handling trauma patients in the Emergency Room, it is not uncommon to cause discomfort and/or dissatisfaction from patients and their families. Doctors as health workers in carrying out their profession sometimes do not apply ethics and medicolegal optimally, so that they can cause problems for the patients they treat. Based on this, the problem can be formulated: How is the ethical review applied in the treatment of trauma patients in the Hospital Emergency Room. The purpose of this study was to provide an overview of the application of etiquette to the handling of trauma patients in the Hospital Emergency Room. This research is descriptive analytic with cross sectional approach. The research population is doctors who work in the Emergency Installation of RSI Banjarnegara. Data was obtained by looking at medical record data, especially patient examination sheets in the ER, observing directly the services of doctors in the Emergency Room and/or online using a questionnaire g-form. Based on the results of the study, it can be concluded that most of the doctors who work in the Emergency Installation of RSI Banjarnegara apply ethical medico-legal handling of trauma patients.